Genetic diversity of multidrug resistant Staphylococcus aureus isolated from clinical and non clinical samples in Egypt - Bendary, M M; Solyman, S M; Azab, M M; Mahmoud, N F; Hanora, A M (Cellular and Molecular Biology, 2016)
In recent years, the increasing incidence of diseases caused by Staphylococcus aureus (S. aureus) has been noted in the university hospitals of El-Sharkia and Assuit governorates - Egypt. Therefore, we studied the genetic relatedness of multidrug resistant S. aureus isolates from different sources in the above mentioned governorates. One hundred and fifty six S. aureus isolates were divided into 5 different groups, 1 non clinical isolates from different food products and 4 different clinical isolates of human and animal sources in the 2 different governorates. Epidemiological characteristics of 156 S. aureus isolates were determined by phenotypic methods including quantitative antibiogram typing and biofilm production. Genetic typing of 35 multidrug resistant (MDR) isolates (7 from each group) based on 16S rRNA gene sequence, virulence and antimicrobial resistance gene profiles was done. The genetic relatedness of the highest virulent strain from each group was detected based on different single locus sequence typing and multi-locus sequence typing (MLST). S. aureus strains isolated from different sources and geographical areas showed high diversity. The genetic typing revealed different sequence types and different sequences of coa and spa genes. S. aureus isolates were found highly diverse in Egypt.